Where We Are Now –The Presence and Importance of International Students to Universities in the United States - Hegarty, Niall (Journal of International Students, 2014)
This paper highlights the importance of international students to the United States by discussing their impact and necessity to U.S. universities. International student enrollment is a major industry of importance to the U.S. economy and despite arduous visa processes and diminished job prospects their enrollment numbers continue to grow. The Institute of International Education (2012) reports that a lack of funding to public universities has increased their reliance on the revenue provided by international students while private universities also seek to bolster their position in the face of increased international competition. The importance of international students in under-enrolled majors, their necessity as a vital revenue stream for universities and the challenges faced by both student and host university are also discussed. The author provides recommendations for improving the educational experience of international students through improved relationships with university constituents in order to maintain the attractiveness and competitiveness of the U.S.